An audit of sharps injuries in clinical skills simulation wards at a UK university. Issue 9 (2nd September 2022) - Hambridge, Kevin; Endacott, Ruth; Nichols, Andrew
Abstract : Background/Aims: Healthcare students are at high risk of sharps injuries, which can negatively impact their confidence and wellbeing. This study audited three clinical skills simulation wards at a UK university to determine the incidence of sharps injuries in this educational setting. Methods: An audit of sharps injuries sustained in three clinical skills simulation wards was conducted, including data from 2008–2016. The authors developed an audit tool to collect data on the number of incidents that occurred, the type of individual involved and the nature of the incident. Results were analysed to compare the incidence of general injuries and sharps injuries among healthcare students and staff. Results: A total of 46 incidents were recorded across the three wards during the 8-year period. Sharps injuries were by far the most common type of injury, comprising 69.6% of recorded incidents, followed by fainting at 19.6%. The highest proportion of general injuries (56.5%) and sharps injuries (59.4%) occurred among nursing students. However, the association between incidents and type of individual involved was not statistically significant Conclusions: Sharps injuries were the most common type of incident in the clinical skills simulation wards, with student nurses being at highest risk. Intervention is needed to improve safety in this educational setting, including sharps handling training, with greater focus on existing regulations.